EXECUTIVE FIXED SALARY ON RISK TAKING AMONG THE LISTED COMMERCIAL BANKS IN KENYA - Njogu, Lucy Wanjiru; Gekara, Dr.Mouni; Waititu, Dr. Gichuhi A.; Omido, Dr. Karim (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of this study was to determine the effects of executive fixed salary on risk taking among the listed commercial banks in Kenya. Methodology:The study used an Epistemology research philosophy, causal research design was adopted whereby panel data approach was used. The target population for this study were the 11 listed banks on the NSE. Secondary Data for the year 2010 to 2015 was collected from the NSE handbook. Data collected was analyzed using descriptive statistics which included means and standard deviations. Inferential statistics such as Pearson correlation and panel regression was also used. The results were presented in form of tables, figures, charts, graphs and trend lines. Results: The study findings revealed that the results indicated that Regression analysis indicated that Executive Fixed Salary and risk taking were negatively and significantly related. Policy recommendation: The study recommended that banks might want to raise their executive salary bases on their executive staff as this will automatically lead to decreased risk in banks.